Study of stability of semi-solid drug "Probioskin" for skin application in the process of storage - Solovyova, Alina; Kaliuzhnaia , Olga (Annals of Mechnikov's Institute, 2021)
Introduction. Currently, there are no means for the treatment of dermatological diseases in the domestic pharmaceutical market with the simultaneous correction and maintenance of the skin microbiome. We have developed a combined preparation with a probiotic component for the treatment of dermatological diseases in the form of an emulsion under the conditional name "Probioskin" with anti-inflammatory, antimicrobial, regenerating, emollient action. The development of a new medicinal product requires a study of the stability of its samples during storage by assessing all the quality indicators included in the ICU project. At the same time storage conditions and expiration date are specified. The aim of the study was to investigate the stability of Probioskin emulsifier during storage. Materials and methods. Objects of research - samples of emulgel "Probioskin" in a tube №1 of 30 g, which were placed for storage in a dry place protected from light at the following temperatures: from +15° C to +25° C (room temperature) and from +8° С to +15° С (cool place) for 18 months; also due to the presence of probiotic component in the drug, the third mode was chosen - from + 2° to + 8° C (refrigerator conditions). Identification and quantification of dexpanthenol in the preparation was performed by liquid chromatography with mass spectrometry. On the chromatograms of the test solution obtained by quantification of dexpanthenol, the retention time of the main peak should coincide with the retention time of this peak on the chromatogram of the reference solution. Identification of lactic acid was performed using characteristic reactions to lactate ion (lactate test in accordance with the requirements of SPU, 2.3.1 and lactate ion test using a method based on the interaction of lactic acid and oxidant in an acidic environment). Determination of the quantitative content of lactic acid was performed by the method of acid-base titration. For this purpose, the back titration method recommended by the European Pharmacopoeia for the quantification of lactic acid was used. Identification of lactobacilli was performed by microbiological methods based on a combination of macroscopic and microscopic properties. Bacterioscopic control was performed by viewing smears prepared from samples of dissolved drug and Gram-stained. Bacteriological control - by sowing on a thick medium MRS-4 and liquid medium MRS-1. The number of live lactobacilli was determined by surface seeding on Petri dishes with dense MRS-4 medium, after 48 h of incubation at a temperature of (37 ± 1) °C, colonies grown on the surface of the medium were counted and the number of live lactobacilli expressed in CFU was calculated in 1 ml of the preparation. Microbiological tests to determine the number of contaminating microorganisms were performed according to SPU. Results and discussion. In order to study the stability of the drug, to establish storage conditions and shelf life, we have produced and put into storage several batches of the drug. Surveys on compliance with the requirements of the QCM project were conducted every 3 months. The results of the analysis of the emulgel "Probioskin" are shown in tables 2, 3, 4. Determination of quality indicators of drug samples for 18 months at all storage temperatures showed non-compliance with one or more indicators. Thus, the recommended shelf life of Probioskin emulsifier is 12 months at temperatures from +8° C to +15° C or from + 2° to + 8° C, but taking into account the presence of live microorganisms in the drug and the results of our storage studies in refrigerator conditions are a priority. For these conditions, the quality of the drug during 12 months of observation did not change compared with the results at the time of manufacture. This indicates a rationally justified composition of the drug and its production technology. Conclusion. The following quality indicators of the drug are selected in the specification of Probioskin emulsifier: description, identification of dexpanthenol, lactic acid, lactobacilli, pH, homogeneity, weight of packaging, microbiological purity, quantitative determination of dexpanthenol, lactic acid, lactobacilli. A study of the stability of the emulsion "Probioskin" during storage at the following temperatures: from +15° C to +25° C, from +8° C to +15° C, from + 2° to + 8° C. It is proved that the drug is stable during storage at temperatures from +8° C to +15° C and from + 2° С to + 8° C for 12 months. DOI: 10.5281/zenodo.5761544